The value of `lim_(h->0) (sin(pi+h) - sin pi)/h` has to be determined.

`lim_(h->0) (sin(pi+h) - sin pi)/h`

=> `lim_(h->0) (sin(pi+h) - 0)/h`

=>` lim_(h->0) (sin pi*cos h + cos pi*sin h - 0)/h`

=> `lim_(h->0) (0*cos h + (-1*sin h) - 0)/h`

=> `lim_(h->0) (-1*sin h)/h`

=>` -1*lim_(h->0) sin h/h`

...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The value of `lim_(h->0) (sin(pi+h) - sin pi)/h` has to be determined.

`lim_(h->0) (sin(pi+h) - sin pi)/h`

=> `lim_(h->0) (sin(pi+h) - 0)/h`

=>` lim_(h->0) (sin pi*cos h + cos pi*sin h - 0)/h`

=> `lim_(h->0) (0*cos h + (-1*sin h) - 0)/h`

=> `lim_(h->0) (-1*sin h)/h`

=>` -1*lim_(h->0) sin h/h`

=> -1

**The value of `lim_(h->0) (sin(pi+h) - sin pi)/h = -1` **